Parental and School Influences on Character Attributes Among Chinese Adolescents - Zhu, Xiaoqin; Shek, Daniel T. L.; Yu, Lu (Frontiers in Pediatrics, 2022)
Objectives: While there are many theoretical propositions on parental and school impacts on character formation among adolescents, limited empirical evidence is available. To fill the research gaps, this study examined how parental factors (e.g., behavioral control, support, parent–child relationship, and psychological control) and school factors (teacher–student relationship and student–student relationship) affect adolescents’ character attributes in the areas of “treating others well,” “self-discipline and law-abidance,” and “traditional Chinese virtues,” from both child and parent perspectives. Method: We used survey data collected from 2,472 Chinese adolescents (Mean age = 14.76 ± 1.82 years; 1,271 girls) and 412 Chinese parents (Mean age = 45.68 ± 6.53 years; 313 mothers) in Hong Kong. Results: Structural equation modeling revealed significant positive effects of positive parental factors and relational factors in school on children’s character attributes. However, psychological control as the indicator of negative parenting did not serve as a negative predictor of adolescents’ character attributes. Conclusion: These findings shed light on the unique contribution of different parental and school factors to character development among Chinese adolescents. The findings also imply the importance of promoting ecological assets in family and school through parent and teacher training in effective character education, which is essential for children and adolescents’ healthy development.